THE IMPLEMENTATION OF TECHNOLOGY IN TNE CONTINUING TEACHER EDUCATION OF THE USA - Shchur, N.M. (Journal of Information Technologies in Education (ITE), 2012)
The content of the National Educational Technology Standards has been analyzed, the experience of implementing technology in the system of the continuing teacher education of the USA has been explored, the advantages and disadvantages of using digital tools in the process of the professional teacher development have been defined.